Efficiency of Recreational Services in Najaf Region, A Field Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Recreational land use in cities represents a vital service for society, whose importance has grown with urban expansion and the increasing challenges of pollution, noise, traffic congestion, and rising urbanization, which have resulted in population growth. These factors drive planners to prioritize recreational areas to address the growing need for improving quality of life by fulfilling spiritual and psychological needs.Furthermore, recreational areas form an economic sector that supports infrastructure development, reduces unemployment, and offers educational and social benefits. This study focuses on evaluating the functions and efficiency of recreational services in the Najaf region.The core research problem is: "Assessing the current state of recreational services within the tourism framework of the Najaf region through the application of planning standards to determine the efficiency and functional performance of these services." The study’s recommendations play a significant role in raising awareness among decision-makers in the Najaf Investment Authority and related service departments about the importance of prioritizing recreational and tourism services.